Peningkatan Pemahaman Masyarakat tentang Keuangan Syariah di Era Ekonomi Digital Pada SMKS Farmasi Cut Meutia Banda Aceh - Ridha, Ainul; Maulida, Zenitha; Nurbismi, Nurbismi; Astuti, Intan Novia; Vilzati, Vilzati (Pencerah, 2024)
This community service initiative aims to raise awareness among the youth in Aceh, particularly students at SMKS Farmasi Cut Meutia, about the importance and application of Islamic finance in the digital economy. The goal is to enhance their understanding of sharia-based financial systems and empower them to embrace these principles in their future financial decisions. The project involves a one-day outreach program at SMKS Farmasi Cut Meutia Banda Aceh, where 87 students participated in a series of lectures and interactive discussions on Islamic finance, its role in the economy, and the challenges and opportunities in the digital financial landscape. The activity also included an online quiz with prizes to engage participants. The program successfully increased the participants' knowledge of Islamic finance and its practical applications in the digital economy. Most students, previously unfamiliar with Islamic finance, gained both theoretical and practical insights into its principles. The event boosted participants' confidence in understanding and applying these concepts, with many expressing interested in similar. The outreach was limited to a single institution and a small sample size, and thus may not fully represent the broader youth population in Aceh. Future initiatives could expand to include more schools and regions.